Social marketing: influencing behaviors for good. 4th ed. - Lee, Nancy R.; Kotler, Philip (London, 2011)
"This is the definitive textbook for the planning and implementation of programs designed to bring about social change. The authors take key marketing principles and show readers how to apply them to campaigns and efforts to improve health, decrease injuries, protect the environment, build communities, and enhance financial well-being. Social marketing has grown in its sophistication and application to a wider array of social problems, and the Fourth Edition captures the momentum and excitement of this burgeoning field."